Microstructural change of 2LiBH(4)/Al with hydrogen sorption cycling: Separation of Al and B - Kim, Ji Woo; Friedrichs, Oliver; Ahn, Jae-Pyoung; Kim, Do Hyun; Kim, Seul Cham; Remhof, Arndt; Chung, Hee-Suk; Lee, Jehyun; Shim, Jae-Hyeok; Cho, Young Whan; Zuettel, Andreas; Oh, Kyu Hwan (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
Using transmission electron microscopy, microstructures of 2LiBH(4)/Al are investigated during the hydrogen cycling (2LiBH(4) + Al <-> 2LiH + AlB2 + 3H(2)). Mechanically, ball milled 2LiH/AlB2 mixture shows a homogeneous phase distribution. For the hydrogen absorption, the decomposition of AlB2 and the formation of 2LiBH(4) occur simultaneously. During the hydrogen cycling, the incomplete formation of AlB2 results in a spatial separation of Al and B. A lack of reactive B from AlB2 results in a limited formation of LiBH4, which leads to the capacity loss of the system. (C) 2009 Published by Elsevier Ltd. on behalf of Acta Materialia Inc.
Keywords: ELECTRON-MICROSCOPY; SODIUM ALANATE; STORAGE; LIBH4; COMPOSITES; TI; MGH2